2022
DOI: 10.3390/agriculture12010106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inorganic Metal (Ag, Cu) Nanoparticles on the Quality of Seeds and Dried Rapeseed Sprouts

Abstract: The present study focuses on the impact of copper and silver nanoparticles on the chemical composition and physical properties of rapeseeds and rape sprouts. The seeds and sprouts were obtained from winter rape grown in a three-year cultivation (2018–2020) treated with silver (AgNP) and copper (CuNP) nanoparticles. In addition, the effect of the freeze-drying temperature (20; 40; 60 °C) on selected properties of the sprouts was studied. Spraying growing plants with nanoparticles resulted, in most cases, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The synthesis and accumulation of many antioxidants, including phenolic acids, flavonoids, vitamin C, carotenoids, glutathione, etc., scavenge ROS and act as a natural defense mechanism for plants against stress [ 83 , 84 , 85 , 86 , 87 ]. Moreover, they also are antimicrobial and, therefore, effective against fungal and bacterial infections and plant pests [ 88 ]. In the current study, ZnO nanoparticle treatment reported higher antioxidant activity in plants by the ABTS assay in both hydroponic and foliar application systems, as compared with media and water controls, while CuO treatment on plants under the hydroponic system did not demonstrate any significant variation in media control but was effective on plants under foliar treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The synthesis and accumulation of many antioxidants, including phenolic acids, flavonoids, vitamin C, carotenoids, glutathione, etc., scavenge ROS and act as a natural defense mechanism for plants against stress [ 83 , 84 , 85 , 86 , 87 ]. Moreover, they also are antimicrobial and, therefore, effective against fungal and bacterial infections and plant pests [ 88 ]. In the current study, ZnO nanoparticle treatment reported higher antioxidant activity in plants by the ABTS assay in both hydroponic and foliar application systems, as compared with media and water controls, while CuO treatment on plants under the hydroponic system did not demonstrate any significant variation in media control but was effective on plants under foliar treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The DPHH assay failed to reveal any significant difference in the antioxidant activity between the nanoparticle-treated plants, though the activity was significantly higher as compared with water and media controls. Thus, an increased antioxidant activity among the nanoparticle-treated plants signifies better tolerance towards infections and pests [ 88 , 89 ]. Similar reports are published in rice, cauliflower, and tomato after copper and cabbage, cauliflower, tomato, black mustard, and pepper after zinc fertilization, respectively [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations